A Modified Method in Laparoscopic Peritoneal Catheter Implantation: The Combination of Preperitoneal Tunneling and Pelvic Fixation. (15th May 2013) - Gunes, Mehmet Emin; Uzum, Gungor; Koc, Oguz; Duzkoylu, Yiğit; Kucukyilmaz, Meltem; Sari, Yavuz Selim; Tunalı, Vahit; Kose, Sennur
Abstract : Introduction . Continuous ambulatory peritoneal dialysis (CAPD) is widely accepted for the management of end-stage renal disease (ESRD). Although not as widely used as hemodialysis, CAPD has clear advantages, especially those related to patient satisfaction and simplicity. Peritoneal dialysis (PD) catheter insertion can be accomplished by several different techniques. In this study, we aimed to evaluate our results obtained with peritoneal dialysis catheter placement by combination of pelvic fixation plus preperitoneal tunneling. Material and Methods . Laparoscopic peritoneal catheter implantation by combining preperitoneal tunneling and pelvic fixation methods was performed in 82 consecutive patients with end-stage renal disease. Sex, age, primary disease etiology, complications, mean duration of surgery, mean duration of hospital stay, morbidity, mortality, and catheter survival rates and surgical technique used were assessed. Analysis of catheter survival was performed using the Kaplan-Meier method. Results . Mean follow-up period was 28.35 ± 14.5 months (range of 13–44 months). Mean operative time was 28 ± 6 minutes, and mean duration of hospital stay was 3 ± 1 days. There were no conversions from laparoscopy to other insertion methods. None of the patients developed serious complications during surgery or the postoperative period. No infections of the exit site or subcutaneous tunnel, hemorrhagic complications, abdominal wall hernias, or extrusion of the superficial catheter cuff was detected. No mortality occurred in this series of patients. Catheter survival was found to be 92% at 3 years followup. Conclusions . During one-year followup, we had seven patients of migrated catheters due to separation of pelvic fixation suture from peritoneal surface, but they were reimplanted and fixated again laparoscopically with success. Over a three-year followup period, catheter survival was found to be 92%. In the literature, similar catheter survival rates without combination of the two techniques are reported. As a conclusion, although laparoscopic placement of PD catheters avoids many perioperative and early complications, as well as increasing catheter free survival period and quality of life, our results comparing to other studies in the literature indicate that different laparoscopic placement methods are still in debate, and further studies are necessary to make a more accurate decision.